An Environmental DNA Survey on Distribution of an Endangered Salmonid Species, Parahucho perryi, in Hokkaido, Japan - Mizumoto, Hiroki; Mitsuzuka, Takashi; Araki, Hitoshi (Frontiers in Ecology and Evolution, 2020)
For protecting endangered species, precise understanding of their distribution is crucial. However, it is often very difficult to estimate at a large scale with conventional methods (e.g., casting nets or electrofishing for aquatic species) because of their low densities in the wild. Sakhalin taimen (Parahucho perryi) is one of the largest and most critically endangered freshwater salmonid fishes in the world. In this study, we applied an environmental DNA (eDNA) detection system for this species to 120 rivers in Hokkaido, the second largest main island of Japan. We successfully detected eDNA from Sakhalin taimen in seven rivers (5.8%). Although these rivers were widely distributed across the island, more than 95% of the total amounts of eDNA were detected from region-A and -I, indicating that local populations in the other regions of Hokkaido are very small and on the brink of extinction. In addition, principal component analyses based on the eDNA-based estimation of Sakhalin taimen distribution and GIS revealed their distribution determinants including limited topographic relief of watershed as well as presence of wetlands and lagoons. Our results suggest that eDNA-based detection systems are an efficient means of monitoring the population status of endangered freshwater species at large scales.